Effects of Plant Extracts on Bacterial Isolates from Infections of the Female Genital Tract - Sundus Adil Naji,; Hayder T. Qaddoori, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Fifty samples of female genital secretions were collected from a group of women whose age ranges from 15 to 50 years old at Al-Batool Hospital for Maternity and Children. The isolates Escherichia coli, Staphylococcus aureus, Candida albicans, and Staphylococcus epidermidis were found in the fungal and bacterial cultures of the samples, with percentages of (45, 31, 13, 11), respectively. Positive samples were isolated at the highest rate of 87 percent for samples isolated from people aged 30 to 40. In the case of pregnancy, there is an increase in the infection rate with fungal and bacterial species, with a percentage of 60 % compared to women. The results of testing the effect of plant extracts (marjoram, chamomile, thyme, peat, and thuja) on isolated bacterial and fungal species showed inhibition diameters (20, 16, 15.5, 13, 10, 10) mm at concentrations (25 %, 50 %, 75 %, 100 %). We discovered that different concentrations of Marjoram, chamomile, thyme, peat, and thuja extracts (25 %, 50 %, 75 %, 100 %) were associated with increased inhibition rates of fungal and bacterial infection with different diameters (10, 12, 15, 16, 20 mm).